Exploring the Relationships between Eating Behaviours, Body Mass Index, Perceived Stress, and Dysmenorrhea among University Students in Malaysia - Shaiful Bahrin, Anisha Alia; Aris, Norliyana (Jurnal Gizi dan Pangan, 2025)
This study employed a cross-sectional design to investigate the interrelationships among eating behaviours (emotional, restrained, and external), Body Mass Index (BMI), perceived stress, and dysmenorrhea among university students. A total of 190 students from three higher education institutions in Kota Kinabalu were recruited via convenience sampling. Data collection was conducted using a self-administered questionnaire comprising sections on sociodemographic background, eating behaviours (DEBQ questionnaire), stress levels (PSS-10 instrument), dysmenorrhoea (WaLIDD score), and anthropometric measurements. Relationships among the variables were analysed using Pearson’s correlation test. The findings showed that most students exhibited external eating behaviours (55.3%), followed by restrained eating (32.1%) and emotional eating (12.6%), with mean±SD scores of 3.16±0.57, 2.84±0.83, and 2.63±0.73, respectively. Most students had a normal weight (60.5%), reported medium stress (80.5%), and experienced moderate dysmenorrhea (51.1%), with corresponding means of 22.31±4.40 kg/m² for BMI, 20.89±4.96 for perceived stress, and 5.93±2.59 for dysmenorrhea severity. The restrained eating was significantly correlated with BMI (r=0.320, p<0.001). No significant correlations were observed between BMI and emotional or external eating (p>0.05). Emotional and external eating behaviours were significantly correlated with perceived stress (r=0.227; r=0.183) and dysmenorrhoea severity (r=0.223; r=0.288), with all associations significant at p<0.05. In conclusion, the exploratory findings highlight interrelated associations among eating behaviours, BMI, perceived stress, and dysmenorrhea. The results suggest potential interactions between eating patterns and body composition, with menstrual discomfort and psychological stress possibly influencing eating behaviours. These findings underscore the need for integrated university-based programmes that promote mindful eating, stress management, and menstrual health to enhance students’ well-being and academic performance.